2019
DOI: 10.1038/s41598-019-50905-7
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structure and electronic properties of beryllium doped boron clusters: A planar BeB16− cluster motif for metallo-borophene

Abstract: Beryllium-doped boron clusters display essential similarities to borophene (boron sheet) with a molecular structure characterized by remarkable properties, such as anisotropy, metallicity and high conductivity. Here we have determined low-energy structures of BeBn0/− (n = 10–20) clusters by utilizing CALYPSO searching program and DFT optimization. The results indicated that most ground states of clusters prefer plane or quasi-plane structures by doped Be atom. A novel unexpected fascinating planar BeB16− clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…al found other GM for B11Bebut the results in the current work showed that isomer is less stable by 16 kcal/mol than 3 at CCSD(T)//def2-TZVP level on structures optimized at PBE0//def2-TZVP. 45 And for completeness, the lowest energy isomer of 3 substituted in position 1 is 12 kcal/mol less stable than 3.…”
Section: One-atom Substitutionmentioning
confidence: 99%
“…al found other GM for B11Bebut the results in the current work showed that isomer is less stable by 16 kcal/mol than 3 at CCSD(T)//def2-TZVP level on structures optimized at PBE0//def2-TZVP. 45 And for completeness, the lowest energy isomer of 3 substituted in position 1 is 12 kcal/mol less stable than 3.…”
Section: One-atom Substitutionmentioning
confidence: 99%
“…In recent years, pure, metal-, and non-metal-doped boron clusters have attracted considerable attention [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] due to their unpredictable chemistry [ 11 , 12 ] and high potential to form novel structures [ 13 ]. Boron is the smallest and lightest semi-metal [ 7 , 14 ] and a neighbor of carbon in the periodic table. It is electron-deficient [ 13 , 15 , 16 , 17 ] and can combine and form novel atomic and molecular boron structures that are planar and quasi-planar [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beryllium-doped boron clusters exhibit remarkable properties such as fluxionality [ 7 , 21 , 31 , 53 , 54 , 55 ] and aromaticity [ 21 , 56 ], as well as characteristics similar to borophene [ 57 ]. Previous theoretical studies have shown that the boron fullerenes B 60 and B 80 can be stabilized by surrounding the boron clusters with beryllium atoms [ 58 , 59 ], which effectively compensates for boron electronic deficiency [ 59 ].…”
Section: Introductionmentioning
confidence: 99%